Debt Rationality, Survival Strategy, Female Online Drivers, Max Weber's Theory of Rationality. - Hasan Ridho Abdillah; Diyah Utami (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the rationality of debt as a survival strategy for female online drivers in Sidoarjo. This phenomenon arises due to vulnerable socioeconomic conditions, characterized by uncertain income, high household needs, and limited access to formal employment. This leads women to choose to work as online drivers. However, their income is insufficient to meet their needs, ultimately leading to debt as a strategy. The research method used was qualitative, using Max Weber's interpretive phenomenological approach, Verstehen, supported by Michael Agar's ethnographic analysis through thematic coding. Data collection techniques were conducted through observation and in-depth interviews with 10 informants using snowball sampling. The results of the study indicate that the socioeconomic conditions of female online drivers are unstable, thus encouraging the emergence of various social action motives, such as fulfilling consumptive, productive, and lifestyle needs. Debt was chosen as a rational strategy because it is considered a quick solution to deal with economic pressures. The practice of debt is carried out through various sources, both formal, semi-formal, and informal, even developing into a